German Muslims and their engagement in participatory culture: reflections on civic and artistic contributions to the public sphere. (30th April 2017) - Soliman, Asmaa
Abstract: This paper examines publics of young German Muslims. Case studies include the singer Huelya Kandemir, the theatre group Uma Lamo and the social network Zahnräder . By focusing on spiritual music publics, theatrical comedy publics and social publics, it tries a new approach to the way in which we understand minority public engagement. In addition to examining the concept of counterpublics, it utilizes the concept of participatory culture, which offers a relevant complement. The study argues that the publics of young German Muslims display multifaceted artistic and civic engagement, which can best be understood in terms of participation in cultural or civic productions and contribution to the wider German public. Features or effects of counterpublics, such as the countering of mainstream representations of minority identities and the offering of alternative discourses, are occasionally reflected in their activities.